Pemanfaatan Teknologi Pendidikan Pada Pembelajaran Berbasis Internet - Erwin Suryaningrat (Institut Agama Islam Negeri Bengkulu, 2014)
This paper aims to discover how an internet presence which is the computer networks that exist around the world. Basically, the internet can bridge barriers of contemporary education. The Internet offers a lot of facilities that can be utilized in many aspects of life, especially the world of education, the utilization of which depends on the practitioner education, institutional capacity and development of the child. But really the internet as a product of technology is not a panacea to solve the problem of educational technology will even cause problems if it is not getting more attention and immerse sunguh professional.